«Մարմնի վերադարձը» և ապամարդկայնացումը թատրոնում - Ա. Է. Խզմալյան (ՀՀ ԳԱԱ հրատ.)
Возвращение к телоцентризму стало осью художественных изысканий XIX-XX столетий (искусство Айседоры Дункан и музыкально-двигательная педагогика Эмиля Жак-Далькроза, концепция эвритмии, сценические поиски Адольфа Аппия и Георга Фукса, включая наиболее значимые фигуры театрального авангарда–Роберта Уилсона и Ромео Кастелуччи). Менялась сущность актерского искусства, его роль и место в сценическом пространстве. Return to the body-centrism became the axis of the artistic searches of the 19-20 centuries (from the art of Isadora Duncan and the pedagogy of musical concept through movement of Emile Jaques-Dalcroze, the concept of Eurythmy, the scenic innovations of Adolphe Appia and George Fuks, reaching the most significant figures of the avant-garde theater such as Robert Wilson and Romeo Castellucci). It changes the nature of the actor's art, its role and place in the scenic action and space.
Keywords: Literature; Language and Literature; PN2000 Dramatic representation; The Theater